The impact of online office on social anxiety among primary and secondary school teachers—Considering online social support and work intensity - Xie, Yating (Frontiers in Psychology, 2023)
The COVID-19 has had a major impact on the global education system. In order to ensure the normal implementation of education courses, governments and education departments around the world have taken corresponding emergency measures. Based on data from 384 validated questionnaires, this study explored the effects of teleworking practices, work intensity, and online social support on social anxiety among primary and secondary school teachers. The results found that teleworking was more likely to cause social anxiety among teachers, while work intensity could promote social anxiety and online social support could reduce the probability of social anxiety. Work intensity can weaken the influence of partner support on social anxiety. Moreover, the model path coefficients differed across work styles. Based on the results, this study proposes some policy recommendations in order to provide theoretical guidance for improving social anxiety among primary and secondary school teachers and promoting the quality of educational work.